Severe obesity is a risk factor for severe obstructive sleep apnea in obese children - Kanokporn Udomittipong (2018)
Objective: To determine the association between degree of obesity and severity of OSA in Thai children Material and Method: The present retrospective study recruited obese children aged 3 to 15 years who had habitual snoring and underwent polysomnography (PSG) between January 2009 and June 2010. Obesity was defined as percentage of ideal weight for height (%W/H) ≥ 120 and was classified as mild (%W/H of 120-139), moderate (140-159), severe (160-199) and morbid (≥ 200). OSA was classified as severe (AHI ≥ 10) and non-severe (AHI < 10). Results: Of 73 obese children, the mean age was 9.92 ± 3.42 years of which 60.3% were boys. The mean ± SD of BMI was 28.38 ± 5.99 kg/m 2 and %W/H ± SD was 162.63 ± 26.26. Gender, age, height, weight and BMI were not significantly different between severe and non-severe OSA groups. However, the %W/H of the severe OSA group (171.38% ± 29.54%) was significantly greater than the non-severe group (157.19% ± 22.68%) (p = 0.02). Severe to morbid obesity (OR 2.80, 95% CI 1.06-7.42; p = 0.038) and enlarged tonsils at least 3+ (OR 3.28, 95% CI 1.22-8.81; p = 0.018) were the risk factors for severe OSA. Conclusion: Severe to morbid obesity was a predicting factor for severe OSA. These results suggested that severely obese children with snoring should have early recognition for severe OSA, which is highly contributing to multiple sequalae.